Effect of grinding on the nutritive value of grain sorghums for fattening steer calves. - Smith, E.F.; Parrish, D.B.; Pickett, A.G. (Kansas Agricultural Experiment Station, 2012)
A digestion trial was conducted with twelve steers which were allotted into three lots of four steers each. A ration of Atlas sorgo silage, cottonseed meal and milo grain was fed in all lots. Whole grain was fed in lot 1, coarsely ground grain to lot 2, and finely ground grain to lot 3.
Keywords: Beef; Nutritive value; Sorghum; Digestibility